De Lubac and Suárez: A Reappraisal - Grumett, David (Theological studies, 2022)
Because of his hostility to pure nature theory, Henri de Lubac has typically been viewed as opposing Francisco Suárez’s metaphysics. His proximate target was the neo-Suárezianism to which he was exposed during his Jesuit formation. Suárez was the Jesuit order’s intellectual founding father and his ideas continued to shape Jesuit philosophy and theology, sometimes in opposition to neo-Thomism. Although de Lubac contested Suárez’s promotion of new and modern theology, Suárez positively informed his approach to key topics: appetite and its end; nature, desire, and the supernatural; the perfection of nature; essences as unique existents; eclecticism; and political resistance.